Molecular identification of Malassezia from the skin scrapings of clinically suspected cases of pityriasis versicolor - Kanchankoti Kiran; Shoorashetty Manohar Rudresh; Yoganand Raksha; Shivanna Ragunatha; Gupta Jyoti; Mandya Rudramurthy Shivaprakash (Indian Journal of Pathology and Microbiology)
Background: Pityriasis versicolor (PV) is caused by a lipophilic fungus belonging to the genus Malassezia. Potassium hydroxide (KOH) mount is most frequently used for screening of cases and culture is the gold standard. KOH lacks sensitivity, and culture is time-consuming and technically demanding. Aim, Settings, and Design: A cross-sectional study was conducted at a tertiary care teaching institution. We aimed to use multiplex-PCR for faster and accurate identification of Malassezia spp directly from skin scrapings of suspected cases of PV. Materials and Methods: The study was conducted on suspected cases of PV over a period of 12 months. The clinical and demographic details were recorded. The skin scrapings were subjected to KOH mount and cultured on Sabouraud’s dextrose agar with an olive oil overlay. Multiplex-PCR targeting 11 Malassezia spp was performed on DNA extracted from skin scrapings. Results: A total of 69 suspected cases of PV were studied. Most patients belonged to metro cities and worked in hot and humid climates. The mean duration of lesions was 18 months, and most had macular and patchy lesions. The sensitivity of KOH and culture was found to be 82.6% and 91.3%, respectively. M. globosa (n = 60, 87%) and M. restricta (n = 3, 4.3%) were isolated in culture. Multiplex PCR detected 85.5% of M. globosa, 5.8% of M. restricta, and 8.7% of mixed infection with M. globosa and M. restricta. M-PCR detected Malassezia in all the samples. Conclusions: M-PCR could identify Malassezia species directly from skin specimens, eliminating the need for culture. M-PCR was accurate, dependable, and exhibited a rapid turnaround time.